2017
DOI: 10.1111/1346-8138.13555
|View full text |Cite
|
Sign up to set email alerts
|

Topics in histopathology of sweat gland and sebaceous neoplasms

Abstract: This article reviews several topics regarding sweat gland and sebaceous neoplasms. First, the clinicopathological characteristics of poroid neoplasms are summarized. It was recently reported that one-fourth of poroid neoplasms are composite tumors and one-fourth are apocrine type lesions. Recent progress in the immunohistochemical diagnosis of sweat gland neoplasms is also reviewed. CD117 can help to distinguish sweat gland or sebaceous tumors from other non-Merkel cell epithelial tumors of the skin. For immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 122 publications
0
8
1
2
Order By: Relevance
“…The results showed that almost a third of our cases (31%) were AR positive. Notably, some studies showed that AR detection may be useful for differentiating sebaceous carcinomas, which are usually reported to be AR positive, from basal cell carcinomas or squamous cell carcinomas, which are usually AR negative, [18][19][20][21] and they described absence of AR expression in microcystic adnexal carcinomas 22 and syringoid eccrine carcinomas. 23 Our data on sebaceous and microcystic adnexal carcinomas are in line with these studies, and extend AR expression to other histotypes, such as hidradenocarcinomas (33%), carcinoma NOS (33%), porocarcinomas (17%) and mucinous carcinomas (one case).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that almost a third of our cases (31%) were AR positive. Notably, some studies showed that AR detection may be useful for differentiating sebaceous carcinomas, which are usually reported to be AR positive, from basal cell carcinomas or squamous cell carcinomas, which are usually AR negative, [18][19][20][21] and they described absence of AR expression in microcystic adnexal carcinomas 22 and syringoid eccrine carcinomas. 23 Our data on sebaceous and microcystic adnexal carcinomas are in line with these studies, and extend AR expression to other histotypes, such as hidradenocarcinomas (33%), carcinoma NOS (33%), porocarcinomas (17%) and mucinous carcinomas (one case).…”
Section: Discussionmentioning
confidence: 99%
“…Other types of skin cancer or adnexal tumors, e.g. sweat gland and sebaceous gland carcinomas [26], non-melanoma nail neoplasms [27], keratoacanthoma [28], Merkel cell carcinoma (APUDoma) [29], are less common and treatment options are varying. Of the non-melanoma skin cancers, BCC is the most abundant (approx.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that sebocytes of ectopic sebaceous glands are possibly under hormonal regulation, as hormone receptors (ER, PgR, and AR) are known to be expressed in normal dermal sebaceous glands and in some sebaceous neoplasms. 13 -17 Our cases immunohistochemically exhibited expression of the ER (7/8) and AR (5/8) in esophageal ectopic sebaceous glands, regardless of their sex. All of the 3 AR-negative cases had been biopsied more than 10 years before, and the immunogenicity of the AR might have decreased over time.…”
Section: Discussionmentioning
confidence: 72%